Pre-clinical efficacy of African medicinal plants used in the treatment of snakebite envenoming: A systematic review. (1st March 2023) - Bala, Auwal A.; Mohammed, Mustapha; Umar, Saifullahi; Ungogo, Marzuq A.; Al-Kassim Hassan, Mohammed; Abdussalam, Umar S.; Ahmad, Mubarak Hussaini; Ishaq, Daha U.; Mana, Dillos; Sha'aban, Abubakar; Jatau, Abubakar I.; Jibril, Murtala; et al.
Abstract: The World Health Organization has listed Snakebite Envenoming (SBE) as a priority neglected tropical disease, with a worldwide annual snakebite affecting 5.4 million people and injuring 2.7 million lives. In many parts of rural areas of Africa and Asia, medicinal plants have been used as alternatives to conventional antisnake venom (ASV) due in part to inaccessibility to hospitals. Systemic reviews (SR) of laboratory-based preclinical studies play an essential role in drug discovery. We conducted an SR to evaluate the relationship between interventional medicinal plants and their observed effects on venom-induced experiments. This SR was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The Modified collaborative approach to meta-analysis and review of animal data from experimental studies (CAMARADES) and SYRCLE's risk of bias tools were used to appraise the included studies. Data were searched online in Medline via PubMed, Embase via OVID, and Scopus. Studies reporting in vivo and in vitro pharmacological activities of African medicinal plants/extracts/constituents against venom-induced pathologies were identified and included for screening. Data from the included studies were extracted and synthesized. Ten studies reported statistically significant percentage protection (40–100%) of animals against venom-induced lethality compared with control groups that received no medicinal plant intervention. Sixteen studies reported significant effects ( p  ≤ 0.05) against venom-induced pathologies compared with the control group; these include hemolytic, histopathologic, necrotic, and anti-enzymatic effects. The plant family Fabaceae has the highest number of studies reporting its efficacy, followed by Annonaceae, Malvaceae, Combretaceae, Sterculiaceae, and Olacaceae. Some African medicinal plants are preclinically effective against venom-induced lethality, hematotoxicity, and cytotoxicity. The evidence was extracted from three in vitro studies, nine in vivo studies, and five studies that combined both in vivo and in vitro models. The effective plants belong to the Fabaceae family, followed by Malvaceae, and Annonaceae. Graphical abstract: Image 1 Highlights: A preclinical systematic review was conducted on plants' efficacy against venom. Both in vivo and in vitro models have been utilized in evaluating plants' efficacy. Some medicinal plants are effective against some snake venom-induced pathologies. The Fabaceae family of plants is more effective against snake venom toxicity.